New hormone receptor-positive breast cancer mouse cell line mimicking the immune microenvironment of anti-PD-1 resistant mammary carcinoma - Carlos Lopez-Otin; Christophe Klein; Chantal Desdouets; Guido Kroemer; Pierre Laurent-Puig; Jonathan Pol; Sophie Mouillet-Richard; Gautier Stoll; Isabelle Martins; Maria Perez-Lanzon; Vincent Carbonnier; Pierre Cordier; et al. (Journal for ImmunoTherapy of Cancer, 2023)
Background Progress in breast cancer (BC) research relies on the availability of suitable cell lines that can be implanted in immunocompetent laboratory mice. The best studied mouse strain, C57BL/6, is also the only one for which multiple genetic variants are available to facilitate the exploration of the cancer-immunity dialog. Driven by the fact that no hormone receptor-positive (HR+) C57BL/6-derived mammary carcinoma cell lines are available, we decided to establish such cell lines.Methods BC was induced in female C57BL/6 mice using a synthetic progesterone analog (medroxyprogesterone acetate, MPA) combined with a DNA damaging agent (7,12-dimethylbenz[a]anthracene, DMBA). Cell lines were established from these tumors and selected for dual (estrogen+progesterone) receptor positivity, as well as transplantability into C57BL/6 immunocompetent females.Results One cell line, which we called B6BC, fulfilled these criteria and allowed for the establishment of invasive estrogen receptor-positive (ER+) tumors with features of epithelial to mesenchymal transition that were abundantly infiltrated by myeloid immune populations but scarcely by T lymphocytes, as determined by single-nucleus RNA sequencing and high-dimensional leukocyte profiling. Such tumors failed to respond to programmed cell death-1 (PD-1) blockade, but reduced their growth on treatment with ER antagonists, as well as with anthracycline-based chemotherapy, which was not influenced by T-cell depletion. Moreover, B6BC-derived tumors reduced their growth on CD11b blockade, indicating tumor sustainment by myeloid cells. The immune environment and treatment responses recapitulated by B6BC-derived tumors diverged from those of ER+ TS/A cell-derived tumors in BALB/C mice, and of ER– E0771 cell-derived and MPA/DMBA-induced tumors in C57BL/6 mice.Conclusions B6BC is the first transplantable HR+ BC cell line derived from C57BL/6 mice and B6BC-derived tumors recapitulate the complex tumor microenvironment of locally advanced HR+ BC naturally resistant to PD-1 immunotherapy.